2005
DOI: 10.1080/17453670510041547
|View full text |Cite
|
Sign up to set email alerts
|

Poor results after augmenting autograft with xenograft (Surgibone) in hip revision surgery

Abstract: Background Surgibone Unilab is prepared from bovine bone and contains hydroxyapatite and protein. It is supposed to be immunogenically inert but the protein could be antigenic in man.Patients and methods We followed 27 patients for an average of 2.5 (1-5) years, all of whom had received Surgibone mixed with autograft to fill in defects in the acetabulum and the proximal femur in revision hip surgery.Results In 17 patients, there was apparently complete incorporation of the bone graft within 6 months. In 3 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 14 publications
1
28
1
Order By: Relevance
“…Our results found no material-specific reasons for failure of bone substitutes as given in the literature [7,10,30,[35][36][37]. Probably the reasons for failure of substitutes have to be reduced to unspecific reasons like the age of the individual, tissue perfusion (due to sclerosis), and personal habits (smoking), or bony instability.…”
Section: Discussioncontrasting
confidence: 61%
“…Our results found no material-specific reasons for failure of bone substitutes as given in the literature [7,10,30,[35][36][37]. Probably the reasons for failure of substitutes have to be reduced to unspecific reasons like the age of the individual, tissue perfusion (due to sclerosis), and personal habits (smoking), or bony instability.…”
Section: Discussioncontrasting
confidence: 61%
“…These results revealed that the tested xenograft did not have an osteoinductive effect, and hence no effect on bone formation. This was rightfully so since Unilab Surgibone ® was defined as an osteoconductive biomaterial 26) , and one should not expect an osteoinductive effect in the defects during bone regeneration. Therefore, as seen in Table 1, there were no significant differences between the two defect sites with regard to bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The results are generally positive, with only Charalambides et al (8) reporting poor results. The xenograft was investigated in experimentally created cranial defects in rats, and both short-term and longterm results proved that it is biocompatible, osteoconductive and has no important adverse effects on bone regeneration (5,6).…”
Section: Discussionmentioning
confidence: 62%